Blaise Cendrars the invention of life - Robertson, Eric 1965- (Reaktion Books, 2022)
In 1912 the young Frederic-Louis Sauser arrived in France, carrying an experimental poem and a new identity: Blaise Cendrars was born. Over the next half-century, Cendrars wrote innovative poems, novels, essays, film scripts and autobiographical prose. His ground-breaking books and collaborations with artists such as Sonia Delaunay and Fernand Leger remain astonishingly modern today. Cendrars's writings reflect his insatiable curiosity, his vast knowledge which was largely self-taught, and his love of everyday life. In this new account Eric Robertson examines Cendrars's work against a turbulent historical background and reassesses his contribution to twentieth-century literature. Robertson shows how Cendrars is as relevant today as ever before, and deserves a wider readership in the English-speaking world
Keywords: Cendrars, Blaise -- 1887-1961; Cendrars, Blaise / 1887-1961 / https://isni.org/isni/0000000121415537; Authors, French / 20th century / Biography; Authors, Swiss / 20th century / Biography; Cendrars, Blaise / 1887-1961; Authors, French; 1900-1999; Biographies; Biografie